PATIENT-CENTRED SCREENING FOR PRIMARY IMMUNODEFICIENCY, A MULTI-STAGE DIAGNOSTIC PROTOCOL DESIGNED FOR NONIMMUNOLOGISTS: 2011 UPDATE - E. de Vries; A. A. Cardona; A. H. Abdul Latiff; R. Badolato; N. Brodszki; A. J. Cant; J. Carbone; J. T. Casper; A. Ciznar; A. V. Cochino; B. Derfalvi; G. J. Driessen; et al. (Медицинская иммунология, 2014)
Abstract. Members of the European Society for Immunodeficiencies (ESID) and other colleagues have updated themulti-stage expert-opinion-based diagnostic protocol for non-immunologists incorporating newly defined primary immunodeficiency diseases (PIDs). The protocol presented here aims to increase the awareness of PIDs among doctors working in different fields. Prompt identification of PID is important for prognosis, but this may not be an easy task. The protocol therefore starts from the clinical presentation of the patient. Because PIDs may present at all ages, this protocol is aimed at both adult and paediatric physicians. The multi-stage design allows cost-effective screening for PID of the large number of potential cases in the early phases, with more expensive tests reserved for definitive classification in collaboration with a specialist in the field of immunodeficiency at a later stage.